1998
DOI: 10.1042/cs0940657
|View full text |Cite
|
Sign up to set email alerts
|

Colour Doppler Sonographic Diagnosis of Upper Limb Venous Thromboses

Abstract: 1. Upper limb venous thromboses are considered to be a rare event, but in large hospitals with a lot of patients who receive aggressive intravenous therapy the number of thromboses seem to increase. 2. We have analysed all the cases of upper limb venous thrombosis which occurred at the Essen University Hospital between the years of 1992-1996. All patients were examined using colour Doppler sonography. 3. Out of 827 patients that were examined, a thrombosis was diagnosed in 334 cases. The subclavian vein was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
1
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 3 publications
2
16
1
7
Order By: Relevance
“…[10] We diagnosed UEDVT in 89 out of 70,751 adult patients ≥20 years (0.13%), and we identified UEDVT, which represented 12% of all cases of DVT during this period, in hospitalized patients at an approximate rate of 1.3 per 1000 patients per year. The prevalence of UEDVT that we observed among hospitalized patients was slightly lower than that reported by Kröger et al [17] and Mustafa et al [8] A possible explanation for the lower UEDVT prevalence in our study could be that we reported only symptomatic UEDVT in a rather low number of patients with CVC. The frequency of UEDVT we reported probably grossly underestimates the true number of cases because imaging tests for UEDVT were always performed on symptomatic patients in our series.…”
Section: Discussioncontrasting
confidence: 85%
See 3 more Smart Citations
“…[10] We diagnosed UEDVT in 89 out of 70,751 adult patients ≥20 years (0.13%), and we identified UEDVT, which represented 12% of all cases of DVT during this period, in hospitalized patients at an approximate rate of 1.3 per 1000 patients per year. The prevalence of UEDVT that we observed among hospitalized patients was slightly lower than that reported by Kröger et al [17] and Mustafa et al [8] A possible explanation for the lower UEDVT prevalence in our study could be that we reported only symptomatic UEDVT in a rather low number of patients with CVC. The frequency of UEDVT we reported probably grossly underestimates the true number of cases because imaging tests for UEDVT were always performed on symptomatic patients in our series.…”
Section: Discussioncontrasting
confidence: 85%
“…[6,9,11,15] As the use of CVC and pacemaker wires has increased, their role in the etiology of UEDVT has become more prominent. [6][7][8][10][11][12]14,17] This association was clearly evident in the present study in which only 19% of our patients had CVC. In contrast, Kröger et al [17] and Mustafa et al [8] reported the use of CVC in 33% and 60% of patients with UEDVT, respectively.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Both the subclavian and axillary veins [1][2][3] and the brachial vein may be involved [4]. The frequency of UEDVT varies in different studies, and the proportion is 1-10% of all DVTs [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%